NETIZEN SARCASM IN THE TWITTER COMMENTS COLUMN @RACHELVENNYA: A STYLISTIC STUDY - Wanci, Sri; Faisal, Faisal; Saguni, Suarni Syam (Media Inovasi Pendidikan dan Publikasi, 2025)
This research aims to describe the forms of sarcasm in the Twitter comment column @rachelvennya. This type of research is qualitative and descriptive using Stylistics theory. The data source in this research is written information found in the Twitter comments column @rachelvennya which has (182,360 thousand) followers. This research found that in the social media Twitter @rachelvennya, there are various forms of sarcasm, including, (1) nature sarcasm, (2) action sarcasm, (3) action result sarcasm, (4) appeal sarcasm, and (5) sarcasm. The research results show that there is a pattern of criticism of Rachel's actions, especially in cases of controversy. Netizens use various forms of sarcasm to satirize and criticize actions they deem inappropriate.